Robert Borden: Leadership in Crisis - Taylor, Samuel (Journal of the Royal Nova Scotia Historical Society, 2025)
Robert Borden, the political leader who led Canada through the Great War, has been largely overlooked. This paper attempts to answer two questions: what was Sir Robert Borden’s leadership style and how effective was it?The first portion of the paper provides a brief overview of Borden’s early life and political career. This is followed by an examination of his early tenure as prime minister prior to the outbreak of war, starting with his appointment in 1911 and covering topics such as the naval debate and the associated stonewalling of Borden’s policies by the Liberals. The paper continues by describing Borden’s leadership style and its effectiveness during the First World War by examining notable issues, such as the conscription crisis, the 1917 election, and issues caused by members of his cabinet, including Samuel Hughes. The paper concludes by stating that while Borden’s leadership was ill suited to peacetime and largely overshadowed by more charismatic politicians, he was a capable, methodical, calculating, and determined leader who successfully led Canada through the crucible of the Great War.